Desenvolvimento de novos poliuretanos a partir da valorização direta do líquido da casca da castanha-de-caju - Pereira, Rita de Cassia Sousa (2023)
Polyurethanes (PUs) are ranked 6th in polymer global production due to their wide range of applications. These polymers are traditionally obtained from the polyaddition reaction between polyols and di-isocyanates. Currently, most commercially available PUs is still manufactured from petrochemical resources. In this sense, the first part of this work proposes the preparation of PUs from the direct valorization of Cashew Nut Shell Liquid (CNSL) through a synthetic route developed in three stages: (1) epoxidation of CNSL with peracetic acid formed in situ; (2) synthesis of novel polyols by oxirane ring-opening reaction, using ethanol and ethylene glycol; (3) preparation of PUs by combining polyols with toluene diisocyanate (TDI) at different NCO:OH ratios (1.0, 1.5 and 2.0). All formulations were analyzed by Fourier Transform Infrared Spectroscopy (FT-IR), gel content, and Thermogravimetric Analysis (TGA). Also, PUs were applied onto wood surfaces and their adhesive properties were investigated through lap shear strength tests, using a Universal Testing Machine. Gel content results (90%-100%) indicated that PUs showed a high density of crosslinking. According to the TGA curves, PUs undergo thermal degradation around 270 ºC. Mechanical tests showed that PUs obtained with a lower NCO:OH ratio and from polyols containing primary hydroxyls resulted in adhesives with adhesive efficiency 2.5 times higher than PUs obtained with polyols containing only secondary hydroxyls. In the second part of this work, CNSL and ethylene glycol-based polyol was combined with TDI in three different NCO:OH ratios (0.75; 1.0 and 1.5). The resulting PUs were reinforced with coconut husk fibers in a proportion of 30:70 matrix/reinforcement. The manufactured composites showed high values of gel content (94% to 100%), indicating a strong matrix/reinforcement interaction. Scanning electron microscopy (SEM) did not reveal any interphase separation. TGA results revealed that the bio-composites presented flame retardant properties, with LOI values > 28. Dynamic mechanical analyzes (DMA) showed values of glass transitions of 85 ºC, 95 ºC and 121 ºC for the composites with NCO:OH molar ratios at 0.75, 1.00 and 1.50, respectively. In addition, equibiaxial flexural strength results showed values ranging from 71.2 MPa to 88 MPa. Therefore, the results obtained in the present work suggest that the direct valorization of cashew biomass could be explored as a eco-friendly alternative towards the development of bio-based polyurethanes with suitable thermal and mechanical properties for high performance applications.